2015
DOI: 10.1097/wco.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering spreading mechanisms in amyotrophic lateral sclerosis

Abstract: Although ALS is clinically heterogeneous, a shared characteristic is the focal onset and the progressive extension to all body regions. Being viewed until now as just summation of the increased number of affected neurons, dispersion is now rather considered as the result of a seeded self-propagating process. A sequential regional spreading pattern is supported by the distribution of TDP-43 aggregates in ALS autopsy cases. Electrophysiology and advanced neuroimaging methods also recently provided some evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Overall, our findings may support spread of disease along axonal connections, facilitating propagation to and from structurally and functionally related body regions (32)(33)(34). Spread of disease from neuron to neuron is potentially a uniform feature in neurodegenerative diseases that requires further exploration (35,36).…”
Section: Discussionmentioning
confidence: 54%
“…Overall, our findings may support spread of disease along axonal connections, facilitating propagation to and from structurally and functionally related body regions (32)(33)(34). Spread of disease from neuron to neuron is potentially a uniform feature in neurodegenerative diseases that requires further exploration (35,36).…”
Section: Discussionmentioning
confidence: 54%
“…This would explain why the left frontal medial orbital and left lingual gyri in the ALSci patient group displayed both decreased nodal strength, and increased clustering coefficients relative to ALScc patients. While there are several hypothesized mechanisms for the increased pathological susceptibility of hub regions [Zhou et al, ], one that is consistent with recent proteinopathy findings in ALS [Brettschneider et al, ; Schmidt et al, ] is the transneuronal spread model, in which a toxic agent spreads to regions of high connectivity by propagating along structural connections [Frost and Diamond, ; Pradat et al, ]. Within ALS, 43 kDA TAR DNA‐binding protein (TDP‐43), a hallmark proteinopathopy of ALS and FTLD [Brettschneider et al, ; Neumann et al, ], has been suggested to propagate along structural network connections [Schmidt et al, ], expanding from primary motor cortices toward frontal, and subsequently temporal, regions [Brettschneider et al, ].…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, a similar prion-like domain is present in the FUS/TLS N-terminus (residues 1-239). The evidence for the spread of TDP-43 and FUS/TLS aggregates from cell to cell and its implication for our understanding of the disease have been recently discussed in a series of review articles (Polymenidou and Cleveland 2012;Lee and Kim 2015;Pradat et al 2015). In vitro aggregates formed by recombinant TDP-43 were shown to be able to induce endogenous TDP-43 aggregation when they are transduced in HEK293T cells (Furukawa et al 2011).…”
Section: The Spread Of Tdp-43 and Fus/tls Pathologymentioning
confidence: 99%